The examination and investigation of the subfertile couple. Issue 5 (May 2022) - Jones, Adam; Sood, Akanksha; Ahmed, Maimoona; Modgil, Vaibhav
Abstract: The World Health Organization (WHO) defines infertility as the 'inability of a sexually active, non-contracepting couple to achieve pregnancy in one year'. It is estimated that this can affect 8–12% of couples worldwide Many couples will demonstrate female and male causes for infertility and will seek assistance from clinicians to achieve pregnancy. The assessment of the infertile couple should include detailed history, focused examination and appropriate investigations prior to any intervention. Clinicians with a specialist interest in infertility should perform this evaluation, as part of their regular practice. The aetiology of female and male infertility is broad and can provide a challenge for experienced clinicians. It is important that patients are evaluated in a structured and sequential manner. This article will review and discuss the evaluation of both the infertile female and infertile male.